Genetic variation in skin traits in New Zealand lambs. (9th March 2022) - McRae, Kathryn M; Cooper, Sue M; McEwan, John C; Anderson, Rayna; Bain, Wendy E; Baird, Hayley J; Dodds, Ken G; Clarke, Shannon M; Pickering, Natalie K; Holmes, Geoff
Abstract: BACKGROUND: This study explored the genetic variability in the New Zealand sheep population for economically important skin traits. Skins were collected at slaughter from two progeny test flocks, resulting in 725 skins evaluated for grain strain, flatness, crust leather strength and overall suitability for shoe leather. DNA profiles collected from skins post‐slaughter were matched to individual animals using previously collected high‐density genotypes. RESULTS: Considerable phenotypic variation for skin traits was observed, with around 40% of the skins being identified as suitable for high‐value shoe leather production. Several key traits associated with leather production, including flatness, tear strength, grain strength and grain strain were found to be moderate to highly heritable ( h 2 = 0.28–0.82). There were no major significant genome‐wide association study (GWAS) peaks associated with many of the traits examined, however, one single‐nucleotide polymorphism (SNP) reached significance for the flatness of the skin over the hindquarters. CONCLUSION: This research confirms that suitable lamb skins can be bred for use as high‐value shoe leather. While moderately to highly heritable, skin traits in New Zealand lambs appear to be polygenic with no genes of major effect underlaying the traits of interest. Given the complex nature of these traits, the identification and selection of animals with higher‐value skins may be enabled by geomic selection. © 2022 The Authors. Journal of The Science of Food and Agriculture published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.